Comparison between digital and conventional occlusal indicators. - Wan M. Dizayee; Fahd S. Ikram (Erbil Dental Journal)
Background and objective: Occlusal adjustments are an integral part of any dental restorations; any occlusal discrepancy will affect the masticatory system generally and the occlusal scheme specifically. This unsolved problem may cause restoration and/or tooth fracture, and also may result in TMJ problems.